Study on reactive thrombocytosis in febrile young infants with serious bacterial infection in a tertiary care hospital - Chidhara, Nasreen (International Journal of Contemporary Pediatrics, 2021)
Background: Thrombocytosis associated with multiple, simultaneous causative factors was also reported in many children. Among all patients with infections, osteomyelitis and septic arthritis were associated with higher platelet counts than other infections. This study was done to estimate the prevalence of reactive thrombocytosis among febrile young infants and to assess the utility of platelet count as a potential predictor of serious bacterial infection. Methods: The study was a cross-sectional study conducted in the department of paediatrics, Kanchi Kamakoti child’s trust hospital, Nungambakkam, Chennai. 140 children were included in the study. Venepuncture was done in all these children. Blood sample of 3 ml was collected in an EDTA tube for complete blood count and in another tube 2 ml of blood was collected for CRP. Results: The prevalence of reactive thrombocytosis was 65.8% in the population with serious bacterial infection (SBI). The proportion of children having respiratory symptoms in the study population was 70%, which was the most common system affected. Gastrointestinal, CNS and genito-urinary symptoms were seen in 29.29%, 11.43% and 10.00% of subjects respectively. Other miscellaneous symptoms were reported in 4.29% of the patients. Conclusions: The prevalence of SBI was highest (30.2%) in the 4 to 6 months age group. The prevalence of SBI in 1 to 3 months, 7 months and above age groups was 28.6% and 29% respectively.